Seroprevalence of H.I.V. infection in pregnant women in labor at the Enrique C. Sotomayor gynecological-obstetric hospital - Baquerizo A., Mario; Vega D., Walter; Castro H., Mercedes (Revista Universidad de Guayaquil, 1994)
The purpose of this study was to determine the seroprevalence of HIV infection in pregnant women in labor at the "Enrique C. Sotomayor" Gineco-Obstetric Hospital, with the purpose of implementing the Microelisa test to detect HIV as a routine in the control prenatal or at the time of admission with labor; For this reason, 300 pregnant women in labor were chosen at random, finding that the seroprevalence was 0.33%, a value very lower than those established by international organizations. - From the analysis of the results we can conclude that it is not worth performing routinely. Microelisa tests for HIV in the population served by the "Enrique C. Sotomayor Gynecological-Obstetric Hospital" and that sentinel programs could only be carried out every 6 months to observe the behavior of this disease.